2017
DOI: 10.1037/hea0000527
|View full text |Cite
|
Sign up to set email alerts
|

Spouses’ daily feelings of appreciation and self-reported well-being.

Abstract: Objective Research shows that active support provision is associated with greater well-being for spouses of individuals with chronic conditions. However, not all instances of support may be equally beneficial for spouses' well-being. The theory of communal responsiveness suggests that because spouses' well-being is interdependent, spouses benefit most from providing support when they believe their support increases their partner's happiness and is appreciated. Two studies tested this hypothesis. Methods Stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 19 publications
1
12
0
Order By: Relevance
“…Although the mechanisms of such associations require additional research, it is possible that providing support to a romantic partner aligns with the well‐established benefits of prosocial behaviors, such as volunteering, buying gifts, and doing random acts of kindness, which have been consistently associated with improved well‐being and health for the person engaging in the behavior (Post, ). In support of this idea, Monin and colleagues () found that when spouses believed that they were increasing their partners’ happiness, the association between support provision and the support‐provider's positive affect was strengthened.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Although the mechanisms of such associations require additional research, it is possible that providing support to a romantic partner aligns with the well‐established benefits of prosocial behaviors, such as volunteering, buying gifts, and doing random acts of kindness, which have been consistently associated with improved well‐being and health for the person engaging in the behavior (Post, ). In support of this idea, Monin and colleagues () found that when spouses believed that they were increasing their partners’ happiness, the association between support provision and the support‐provider's positive affect was strengthened.…”
Section: Discussionmentioning
confidence: 98%
“…This study is the first to examine partners’ day‐to‐day experience of providing support to an SM/V with PTSD symptoms. Although prior research using global measures has found support provision to be associated with positive outcomes for the provider (e.g., Monin et al., ), other research documenting feelings of burden in partners of individuals with PTSD symptoms has raised speculations that support provision may be associated with partners’ emotional distress (e.g., Dekel, Goldblatt et al., ; Manguno‐Mire et al., ). Contrary to this latter research, our results indicated that a partner's provision of both instrumental and emotional support was associated with same‐day decreased negative affect and increased positive affect.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…125 For example, perceiving that one's spouse appreciates the support that they receive moderates the association between giving support and self-reported physical symptoms such that greater perceptions of support effectiveness are associated with less physical symptoms. 126 In a similar vein, being acknowledged for the support one gives, which may increase feelings that one's support was effective, is associated with greater well-being (satisfaction with life). 127 In the other direction, signs that one's support was less effective, as evidenced by the receiver's reactions to the support, do not lead to benefits.…”
Section: Support Effectivenessmentioning
confidence: 99%